2008
DOI: 10.1111/j.1537-2995.2008.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational cohort safety study of 5106 platelet transfusions with components prepared with photochemical pathogen inactivation treatment

Abstract: In this cohort study, 99.2 percent of transfusions were without reactions attributed to PLTs. INTERCEPT PLTs exhibited a safety profile similar to that previously reported for conventional PLT components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 19 publications
6
100
0
Order By: Relevance
“…However, we did not detect any trends to indicate that pathogen inactivation of PC affected the frequency of ALI and did detect a significant increase in ventilator-free days among recipients of PC treated with pathogen inactivation during the period of transfusion support. This finding requires confirmation via subsequent prospective clinical trials or large-scale active hemovigilance studies 22,23 before concluding pathogen inactivation of PCs can reduce the severity of concomitant ALI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect any trends to indicate that pathogen inactivation of PC affected the frequency of ALI and did detect a significant increase in ventilator-free days among recipients of PC treated with pathogen inactivation during the period of transfusion support. This finding requires confirmation via subsequent prospective clinical trials or large-scale active hemovigilance studies 22,23 before concluding pathogen inactivation of PCs can reduce the severity of concomitant ALI in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Specifically, Osselaer et al 33 reported a prospective safety study of 5106 transfusions of plts prepared with the INTERCEPT process in five European sites, as used in routine clinical care. The INTERCEPT process was used in place of g irradiation for the prevention of TA-GVHD in all but one site.…”
Section: Interceptmentioning
confidence: 99%
“…We expected the universal use of pathogen-inactivated PCs (PI-PCs) to result in complete cessation of septic transfusion reactions due to PCs as well as in a general decrease in number and severity of transfusion reactions [7,8]. Based on former experiences with production of PI-PCs for clinical trials in the university hospital of Basel, we assumed that an increase in PC collection of approximately 15% would be necessary to provide the amount of PCs that would be requested for transfusion.…”
Section: Introductionmentioning
confidence: 99%